Additively manufactured metamaterials for acoustic absorption: a review - Vignesh Sekar; Wesley J. Cantwell; Kin Liao; Benoit Berton; Pierre-Marie Jacquart; Rashid K. Abu Al-Rub (Virtual and Physical Prototyping)
Noise pollution, a major concern in modern life, contributes to various mental and psychological problems. In this study, we concentrate on the recent developments in metamaterials, particularly additively manufactured acoustic-absorbing metamaterials. These have demonstrated enormous potential for noise reduction across a broad range of frequencies. The current review attempts to classify these additive-manufactured acoustic absorbing metamaterials as perforated, slotted, cellular, and hybrid. Herein, we present a detailed study of the efficiencies and applicability of each subclass, as well as a critique of the experimental research undertaken within each subclass. The review focuses on the subtle features of their operation by evaluating the effect of varying key parameters on the sound absorption capabilities of these metamaterials. Through this comprehensive review, we aim to highlight the current status of this evolving area and motivate more study and innovation in pursuit of effective noise pollution reduction measures.